Tomato rot by Rhizopus microsporus alters native fungal community composition and secondary metabolite production - Napo, Mmanoko; Kock, Alicia; Alayande, Kazeem A.; Sulyok, Michael; Ezekiel, Chibundu N.; Uehling, Jessie; Pawlowska, Teresa E.; Adeleke, Rasheed A. (Frontiers in Microbiology, 2025)
Rhizopus rot is considered one of the most common diseases influencing global production and yield of horticulture commodities. However, the factors contributing to this pattern of prevalence are uncertain. Here, we focused on R. microsporus, which is known to rely on its endosymbiotic bacterium, Mycetohabitans, to produce toxins that interfere with plant development and inhibit the growth of other fungi. We assessed the impact of the symbiotic R. microsporus harboring its endosymbiont as well as the fungus cured of it on: (1) the magnitude of spoilage in tomato fruits, as evaluated by Koch's postulate for pathogenicity, (2) the shifts in native communities of endophytic fungi inhabiting these fruits, as examined by ITS rRNA gene metabarcoding and (3) secondary metabolites generated by these communities, as analyzed using multi-analyte LC-MS/MS. The pathogenicity test showed that the symbiotic endobacterium-containing R. microsporus W2-50 was able to cause tomato fruit spoilage. This was accompanied by decreased relative abundance of Alternaria spp. and an increase in the relative abundance of Penicillium spp. that may have facilitated the observed spoilage. In conclusion, symbiotic W2-50 appeared to facilitate fruit spoilage, possibly through successful colonization or toxin production by its endosymbiont.